REY‐Th‐U Dynamics in the Critical Zone: Combined Influence of Reactive Bedrock Accessory Minerals, Authigenic Phases, and Hydrological Sorting (Mule Hole Watershed, South India). (18th May 2018) - Braun, Jean‐Jacques; Riotte, Jean; Battacharya, Shrema; Violette, Aurélie; Oliva, Priscia; Prunier, Jonathan; Maréchal, Jean‐Christophe; Ruiz, Laurent; Audry, Stéphane; Subramanian, S.
Abstract: The sources of REY‐Th‐U and long‐term mass balance were assessed in the gneissic tropical forested Critical Zone Observatory of Mule Hole, India. The study relies on the characterization of the solid compartments (bedrock, soils, streambed and suspended sediments), on batch leaching experiments of the parent gneiss and on extractions of cation‐exchangeable and iron‐related pools of selected soil samples. The REY‐Th‐U primary reservoir is controlled by monazite, xenotime, thorite, allanite, bastnesite, titanite, apatite, and, to a lesser extent, by zircon. This accessory mineral assemblage was profoundly modified by episodes of metamorphism and hydrothermal activity. Allanite, bastnesite, titanite, and apatite are prone to break down at incipient weathering stage while monazite, xenotime and zircon are resistant minerals. On a long‐term basis, REY are roughly inert in the immature saprolite and depleted in the soil cover and are strongly redistributed among secondary phases. LREE and HREY are mainly controlled by poorly crystallized secondary iron oxides and oxyhydroxides, and, to a lesser extent, by secondary phosphates (e.g., rhabdophane). Th, inert in the saprolite, is controlled by well‐crystallized secondary iron oxides and oxyhydroxides and likely by secondary thorianite (ThO2 ). REY and Th are not easily mobilized during surface processes such as chelation by organic matter and uptake by plants. REY and Th are, by far, exported as suspended sediments associated with iron oxides. The U export by groundwater and suspended sediments dominates over those of streambed sediments and stream. Key Points: Clarifying the source to sink behavior of REY‐Th‐U is important for unraveling Earth surface processes and new ore prospection tools Secondary iron oxides are key REY‐Th‐U carriers in the regolith as well as through adsorption or occlusion Hydrological sorting privileges the REY‐Th‐U export as silts and clays in suspended sediments